1993
DOI: 10.1111/j.1399-6576.1993.tb03782.x
|View full text |Cite
|
Sign up to set email alerts
|

Halothane–associated enhancement of the secondary immune response to sheep erythrocytes in mice: cell transfer studies

Abstract: The effect of halothane anesthesia on the humoral immune response to sheep red blood cells was studied in mice immunized twice, with a 15-day interval. On both occasions, mice were exposed to 1.5% halothane for 40 min immediately after sensitization. Halothane reexposure resulted in increased numbers of IgG-secreting cells (IgG-SC) as well as circulating 7S-serum agglutinins. To examine further whether this effect could be obtained in syngeneic recipients, adoptive transfer experiments employing spleen cells w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…In response to anaesthetic exposure, humoral parameters, such as the number of immunoglobulin G secreting cells, are altered in animal studies [19,20]. Exposure to low concentrations of volatile anaesthetics seems to inhibit predominantly T-helper cell function [11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In response to anaesthetic exposure, humoral parameters, such as the number of immunoglobulin G secreting cells, are altered in animal studies [19,20]. Exposure to low concentrations of volatile anaesthetics seems to inhibit predominantly T-helper cell function [11].…”
Section: Discussionmentioning
confidence: 99%
“…Exposure to low concentrations of volatile anaesthetics seems to inhibit predominantly T-helper cell function [11]. It has been reported that low concentrations of anaesthetics preferentially impair T cell activity, whereas higher concentrations also affect B cells [19,20]. This effect could be explained by impaired T-helper cell activity that adversely affects B cell activity.…”
Section: Discussionmentioning
confidence: 99%
“…Inhalatory anaesthetic may either produce reversible and short-term alterations on cellular functions or cause acute and chronic toxicity as a result of the formation of intermediate and end metabolic compounds (Rice & Fish 1994). Our group studied the effect of several inhalatory anaesthetics on components of the immune response as well as on their functional activities, both in vivo and in vitro in a mouse model (Puig et al 1993(Puig et al , 1995. We found an enhancement of the humoral response upon repeated halothane exposure.…”
mentioning
confidence: 99%
“…activation. Halothane increases the antibody titre 8 , and, as sevoflurane does, it increases the primary and secondary responses 5,8,9,20,21,27 .…”
Section: Il-6mentioning
confidence: 99%
“…Thus, part of the effect of anaesthetics on the immune system would be due to its action on the well-known immunomodulatory effect of glucocorticoids 3 . Diverse in vitro experiments with human immune cells 4 , ex vivo [5][6][7] , in vivo [8][9][10] or animal models have been used to study the effect of anaesthetic drugs on the immune system. .…”
Section: Introductionmentioning
confidence: 99%